Pengaruh Gaya Kepemimpinan terhadap Motivasi Kerja Karyawan pada PT. Barakah Niaga Semen - Andi Abriani Ayu Sari; Nurman Nurman; Tenri Sayu Puspitanigsih Dipoatmodjo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of leadership style on employee work motivation at PT. Barakah Niaga Semen. In this study, the population studied was 30 employees who were also used as samples. The method used is a quantitative approach with simple linear regression analysis, using Statistical Product and Service Solutions (SPSS) software to analyze the data obtained. Data were collected through questionnaires distributed to respondents involved in this study. The results of the analysis show that leadership style has a positive and significant effect on employee work motivation. With a determination coefficient (R2) value of 55.4%, it shows that 44.6% of the variation in employee work motivation can be explained by the leadership style applied in the company. Meanwhile, the remaining 44.6% is influenced by other factors not examined in this study. This finding emphasizes the importance of implementing a good leadership style to improve employee motivation. Therefore, companies are advised to continue to strengthen their leadership style in order to improve work motivation which can ultimately contribute to improving the company's overall performance. This study also provides insight for management to improve work motivation by strengthening the existing leadership style, so as to create a more productive and harmonious work environment.